2019
DOI: 10.1194/jlr.ra119000236
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial immunogenic α-galactosylceramide identified in the murine large intestine: dependency on diet and inflammation

Abstract: Supplementary key words glycolipids • sphingolipids • mass spectrometry • immunology • bacteria • invariant natural killer T cells • Western diet • experimental colitis • influenza A virus • cluster of differentiation 1d Besides recognition of classical major histocompatibility complex class I or II molecules presenting oligopeptides by T lymphocytes, a wide variety of nonclassical nearly monomorphic major histocompatibility complex molecules, including CD1, may be recognized by  and  T cells as Abstract T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 72 publications
0
24
0
Order By: Relevance
“…Infection with IAV also resulted in a shift in glycolipid metabolism. Interestingly, IAV infection altered the synthesis of alpha-galactosylceramides 53 which are known ligands for invariant natural killer T cells and play an important role in the immune system in rodents and humans. 54 It is not clear whether these metabolic changes influence gut homeostasis and function.…”
Section: Impact Of Viral Respiratory Tract Infections On the Gut Micrmentioning
confidence: 99%
“…Infection with IAV also resulted in a shift in glycolipid metabolism. Interestingly, IAV infection altered the synthesis of alpha-galactosylceramides 53 which are known ligands for invariant natural killer T cells and play an important role in the immune system in rodents and humans. 54 It is not clear whether these metabolic changes influence gut homeostasis and function.…”
Section: Impact Of Viral Respiratory Tract Infections On the Gut Micrmentioning
confidence: 99%
“…Conversely, B. fragilis has been reported to have a direct effect on the homeostasis of colonic iNKT cells by providing inhibitory sphingolipids that negatively modulate cell proliferation in the neonatal period . Interestingly, the presence of αGalCers in the murine intestinal compartment is strongly decreased in response to Western‐type diet, dextran sodium sulfate (DSS)‐induced colitis or influenza A virus infection, potentially impacting the function of intestinal iNKT cells . Altogether, these studies support a model by which the commensal microbiota can control the iNKT cell compartment by providing either inhibitory or stimulatory lipid antigens.…”
Section: Nkt Cells In the Intestinal Compartmentmentioning
confidence: 99%
“…More importantly, Lynch et al [ 80 ]. treated high-fat diet-fed mice with sphingolipids (αGalCer), which effectively activated iNKT cells when presented by CD1d on APCs [ 81 ]. They found that three days after treatment with αGalCer, the number of Treg cells in the adipose tissue of wild-type mice was significantly increased, suggesting that the activation of iNKT cells promoted the proliferation and activation of Treg cells.…”
Section: Treg Cells Regulate the Occurrence And Development Of Obesitmentioning
confidence: 99%